Study on high pressure homogenization and high power ultrasound effectiveness in inhibiting polyphenoloxidase activity in apple juice. (March 2018) - Bot, Francesca; Calligaris, Sonia; Cortella, Giovanni; Plazzotta, Stella; Nocera, Francesco; Anese, Monica
Abstract: High pressure homogenization (HPH) and ultrasound with (USct ) or without (US) temperature control were applied to apple juice individually or in combination for inactivating polyphenoloxidase (PPO). Ten passes HPH at 150 MPa were needed to achieve 50% PPO inactivation. USct led to 90% PPO decrease at the longest time (45 min), whereas total enzyme inactivation was achieved by subjecting samples to 6 min US. Results showed that temperature affected enzyme inactivation rather than the process applied. Moreover, the HPH-USct and HPH-US combined treatments led to enzyme residual activities similar to those caused by the application of HPH and USct, and US individual treatments, respectively. US provided to the apple juice less energy density to obtain PPO inactivation than USct and HPH, due to the contribution of the in situ generated heat. Also, US showed the lowest energy consumption, thus confirming its appropriateness. Highlights: High pressure homogenization scarcely affected polyphenoloxidase activity in apple juice. Ultrasound without temperature control effectively inactivated polyphenoloxidase. Ultrasound in situ generated heat mainly contributed most to inactivate polyphenoloxidase. Ultrasound without temperature control was the least energy consuming treatment.